Investigation of the radiation intensity of the discharge components depending on the current - Livia Mesarosh; Месарош Лівіа; Mészáros Lívia; Mikhailo Chuchman; Чучман Михайло; Alexander Shuaibov; Шуаібов Олександр (Scientific and Technical Translations, 2019)
Abstract. The results of spectroscopic studies of a glow discharged plasma at atmospheric pressure in air with an electrode based on distilled water are presented.
https://books.google.ru/books?id=P2iwDwAAQBAJ&printsec=frontcover&hl=ru#v=onepage&q&f=true
Keywords: radiation intensity; discharge; distilled water; spectroscopic studies